Fifth Report on the Excavations of the Roman Fort at Richborough, Kent - Cunliffe, B.W (Reports of the Research Committee of the Society of Antiquaries of London, 1968)
This is the fifth report on excavations by Barry Cunliffe that took place on the site of the Roman fort and amphitheatre at Richborough, in Kent, in the 1960s. Included are descriptions of artefacts such as pottery, coins and buildings, together with an account of the methodology used to unearth these.